# 2x-(2+4x)=3(x+2)+1

## Simple and best practice solution for 2x-(2+4x)=3(x+2)+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 2x-(2+4x)=3(x+2)+1 equation:

2x-(2+4x)=3(x+2)+1
We move all terms to the left:
2x-(2+4x)-(3(x+2)+1)=0
We add all the numbers together, and all the variables
2x-(4x+2)-(3(x+2)+1)=0
We get rid of parentheses
2x-4x-(3(x+2)+1)-2=0

We calculate terms in parentheses: -(3(x+2)+1), so:
3(x+2)+1
We multiply parentheses
3x+6+1
We add all the numbers together, and all the variables
3x+7
Back to the equation:
-(3x+7)

We add all the numbers together, and all the variables
-2x-(3x+7)-2=0
We get rid of parentheses
-2x-3x-7-2=0
We add all the numbers together, and all the variables
-5x-9=0
We move all terms containing x to the left, all other terms to the right
-5x=9
x=9/-5
x=-1+4/5

`